Psychoanalytic conceptual framework: a critical review of creativity in modeling inquiry training - Zaenal Sukawi; Ahmad Khoiri; Sri Haryanto; Denok Sunarsi (Jurnal Konseling dan Pendidikan, 2021)
The conceptual framework of psychoanalysis seeks to explain the nature and development of the personality of students through creative elements, namely motivation, emotions, and other internal creative aspects. Conceptual method of psychoanalytic approach as a determination of the implementation of the inquiry training model through a systematic review. Based on data analysis that: 1) student creativity can be explored through a psychoanalytic approach that expresses new ideas with students' intellectual freedom in the form of inquiry and problem-solving skills in their own way; 2) Creativity is based on Guilford's creative person who is built by conscious and unconscious efforts on neuroscience which gives rise to motivation, energy, ego to do creative ideas; 3) Different ways of creative students become important factors in determining discovery learning models. creativity is part of a personality that is encouraged to be creative if indeed they cannot meet sexual needs directly. Because their needs are not fulfilled, sublimation occurs, and finally, imagination emerges.